Analisis Pengendalian Kualitas Produk Teh Hitam dengan Pendekatan Lean-Six Sigma Method di PT. Teh XY - asih, endang widuri; Rain, La Ode Rahmat; Pohandry, Arie (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2021)
PT. XY tea is a black tea processing company, the problem faced is the presence of tea powder that has a production defect that must be reworked because the water content does not meet the standard (3-4%). The purpose of this study was to analyze the quality control of black tea products by identifying the relationship between the types of waste at the work station and measuring the sigma level value. The method used to identify the interrelationships between wastes is by using the Waste Relationship Matrix and making a control chart graph and then calculating the DPMO value and Sigma Level to measure the level of production capability. The results showed that the largest percentage level for waste that has an influence on other types of waste is waste of motion (22.50%) at the sorting stage, the waste that is often affected is inventory (19.63%) at the milling stage. For the production of quality I black tea, the sigma value is 2.31 with a DPMO value of 210605, meaning that for every one million opportunity there is a possibility of 210605 units of rework products. Meanwhile, for quality III, the sigma value is 2.55 with a DPMO value of 150661.